1990
DOI: 10.1002/cber.19901230432
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resolution of [2,2]Paracyclophanes by High‐Performance Liquid Chromatography on Tris(3,5‐dimethylphenylcarbamates) of Celllulos and Amylose

Abstract: were completely separated into enantiomers at least on one Although one of the reasons for the continuing interest') in the preparation of novel cyclophane systems rests on the stereochemical properties of these bridged aromatics2-4), their utilization as chiral reagents is conspicuously lacking5). This is surprising, since -compared to many classical base derivative 11, the p-nitrophenylhydrazone 12 as well as the methylamino derivative 14, the nitroso compound 16, and the phenanthrenophane 19 are described h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The influence of straight-and branched-chain alcohol's apart from the above-mentioned 2-propanol, ethanol, and methanol were reported recently for Chiralcel OD 24,25 and for Chiralpak AD 16,28 showing good separations. In the present study, we were looking for possibilities to improve the separation and resolution factors of the current analytical method to create an opportunity for a preparative chromatographic separation of the DEP enantiomers.…”
Section: Conditions Affecting Separation By Hplcmentioning
confidence: 82%
See 1 more Smart Citation
“…The influence of straight-and branched-chain alcohol's apart from the above-mentioned 2-propanol, ethanol, and methanol were reported recently for Chiralcel OD 24,25 and for Chiralpak AD 16,28 showing good separations. In the present study, we were looking for possibilities to improve the separation and resolution factors of the current analytical method to create an opportunity for a preparative chromatographic separation of the DEP enantiomers.…”
Section: Conditions Affecting Separation By Hplcmentioning
confidence: 82%
“…The similarity of both CSPs in selectivity toward the DEP enantiomers indicates that the chiral recognition in the case of the small DEP molecules is not essentially influenced by the polysaccha- ride backbone, but by the polar carbamate groups, which can interact with polar groups of racemic compounds through hydrogen bond and dipole-dipole interaction. 27,28 A quantitative comparison between both types of CSPs is difficult, for the weight ratio of support to tris-(3,5-dimethylphenyl carbamate) moieties is not known and intercolumn variability cannot be excluded. 13,29,30 However, it could be shown that the column efficiency, expressed as the number of theoretical plates (N), was superior for Chiralpak AD with three exceptions.…”
Section: Comparison Between Chiralcel Od and Chiralpak Admentioning
confidence: 99%
“…The separation of a series of [2,2]paracyclophanes has been reported on Chiralcel OD and Chiralpak AD. 13 Inspection of the data for methyl, chloro, and fluoro substituted [2,2]paracyclophanes shows that retention on Chiralcel OD is almost insensitive to substitution whereas tremendous changes are observed between fluorine and chlorine on Chiralpak AD, in sharp contrast to what is observed on our rigid structure. These nonpolar compounds are nevertheless poorly separated compared to cyclophanes bearing more polar substituents.…”
Section: Resultsmentioning
confidence: 81%
“…In the ensuing years, many studies were performed to understand how the coated polysaccharide esters and carbamates actually worked [60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Most of the these studies were concerned with the effects of substituents on the benzoate ester or phenylcarbamate rings, the effect of size and shape of various alcohol mobile-phase modifiers, and the systematic variation of solute structure to determine the effects that various structural elements had on the type of interactions between chiral stationary phase and solvent.…”
Section: Structure and Mechanisms Of Operationmentioning
confidence: 99%
“…However, these π-π interactions may be important under reversed-phase conditions, as evidenced by the separation of some β-blockers on CDMPC [11,60,61]. These π-π interactions also offer a possible explanation for the separation of some nonpolar aromatic [2.2]paracyclophanes on ADMPC and CDMPC [11,62].…”
Section: Structure and Mechanisms Of Operationmentioning
confidence: 99%